Photoconducting and photocapacitance properties of Al/p-CuNiO2-on-p-Si isotype heterojunction photodiode - Elsayed, I. A.; Cavas, Mehmet; Gupta, R.; Fahmy, T.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2015)
Thin film of CuNiO2 was prepared by sol gel method to fabricate a photodiode. The surface morphology of the CuNiO2 thin film was investigated by atomic force microscopy (AFM). AFM results indicated that CuNiO2 film was formed from the nanoparticles and the average size of the nanoparticles was about 115 nm. The optical band gap of CuNiO2 film was calculated using optical data and was found to be about 2.4 eV. A photodiode having a structure of Al/p-Si/CuNiO2/Al was prepared. The electronic parameters such as ideality factor and barrier height of the diode were determined and were obtained to be 8.23 and 0.82 eV, respectively. The interface states properties of the Al/p-Si/CuNiO2/Al diode was performed using capacitance-voltage and conductance-voltage characteristics. The series resistance of the Al/p-Si/CuNiO2/Al photo diode was observed to be decreasing with increasing frequency. The diode exhibited a photoconducting behavior with a high photosensitivity value of 1.02 x 10(3) under 100 mW/cm(2). The obtained results indicate that Al/p-Si/CuNiO2/Al can used in optoelectronic device applications. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Optical properties; Photo diode; CuNiO2 thin film